Perspectives on Improving Cohesion Policy Spending - Andrei Sebastian Badea (CES Working Papers, 2011)
The aim of this paper is to reveal and summarize the latest visions and opinions published in articles and academic papers on the evaluation, institutional factors and the future of the European Cohesion Policy. The literature on the economic, territorial and social integration is vast and great emphasize has been put into the techniques, policies and instruments used in achieving these goals. The paper identifies some of the currents of opinion starting from cohesion evaluation methods and heading towards methods, techniques and policies for intervention without claiming to be an exhaustive endeavour. The article concludes with the summarising of the main opinions on the trends, directions and future of the European Cohesion Policy.
Keywords: 330; Cohesion Policy; Territorial Cohesion; Social Cohesion; Structural funds; Institutional performance